©2022 AYDEN Journals 21 EXPLORING THE LINK BETWEEN IDIOSYNCRATIC VOLATILITY AND AVERAGE STOCK RETURNS IN SRI LANKA USING THE FAMA AND FRENCH FIVE-FACTOR MODEL - Jayawardena, S. N.; Rajapakse, M. L. (Ayden International Journal of Banking, Finance and Technology, 2024)
The idiosyncratic volatility puzzle in the asset pricing literature has been a topic of debate for several decades. This study aims to shed light on this puzzle from a South Asian market perspective, specifically in Sri Lanka. Using a sample of 214 nonfinancial firms listed on the Colombo Stock Exchange over a period of 163 months from September 2004 to March 2018, this study examines the impact of idiosyncratic volatility on average stock returns in Sri Lanka. The empirical results suggest that idiosyncratic volatility has a positive and statistically significant impact on average stock returns in the Sri Lankan market. Additionally, the findings reveal that idiosyncratic volatility is high among small stocks that are exposed to lower levels of profits and investments. These results raise questions about why there is a high demand for small stocks in the market. Furthermore, this study provides new evidence on the relationship between idiosyncratic volatility and profitability and investment, which departs from previous studies in this area. The findings of this study have significant implications for investors and policymakers in Sri Lanka and other emerging markets.